Digital mammography performed with computed radiography technology - Jouan, Bernard (European journal of radiology, 1999)
Introduced by Fuji Photo Film Japan in the early 1980s, computed radiography (CR) technology has developed considerably since then to become the mature widely installed technology it is today (about 7500 systems worldwide). Various mammographic examinations require high performance results to which CR complies on demand or following some procedures such as geometrical magnification carried out during the examination. The basic CR principles and digital image processing as well as technical improvements are detailed in this study, which also includes a synthesis of the articles on CR mammographic applications referenced in the bibliography, focusing on strong points, limits and current methods of surpassing these limits. New CR technology development perspectives in mammography and computed assisted diagnosis (CAD) algorithms will allow wider use of this method in the near future.